2011
DOI: 10.2522/ptj.20100372
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Physical Performance and Executive Function in Older Adults With Mild Cognitive Impairment: Gait Speed and the Timed “Up & Go” Test

Abstract: Physical performance speed was associated with executive function after adjusting for age, sex, and age-related factors in sedentary older adults with aMCI. Further research is needed to determine mechanisms and early intervention strategies to slow functional decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
158
4
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(181 citation statements)
references
References 58 publications
13
158
4
6
Order By: Relevance
“…A possible explanation to the marked increases in the functional capacity in our subjects could be related to the improvements observed in the muscle CSA and power output, because a crosssectional study has showed that the functional outcomes are strongly associated with muscle CSA and power output in frail nonagenarians (Casas-Herrero et al 2013). Frailty syndrome is an independent predictor of a decline in cognitive function (Samper-Ternent et al 2008), and frail individuals have an increased risk of becoming cognitively impaired; this decline in cognition over time is more severe in frail subjects compared with non-frail subjects (Buchman et al 2007;SamperTernent et al 2008;McGough et al 2011). In addition, impaired physical outcomes, such as altered gait velocity and muscle weakness, are associated with cognitive impairment (Samper-Ternent et al 2008), and these outcomes are physical domains of frailty (GarciaGarcia et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation to the marked increases in the functional capacity in our subjects could be related to the improvements observed in the muscle CSA and power output, because a crosssectional study has showed that the functional outcomes are strongly associated with muscle CSA and power output in frail nonagenarians (Casas-Herrero et al 2013). Frailty syndrome is an independent predictor of a decline in cognitive function (Samper-Ternent et al 2008), and frail individuals have an increased risk of becoming cognitively impaired; this decline in cognition over time is more severe in frail subjects compared with non-frail subjects (Buchman et al 2007;SamperTernent et al 2008;McGough et al 2011). In addition, impaired physical outcomes, such as altered gait velocity and muscle weakness, are associated with cognitive impairment (Samper-Ternent et al 2008), and these outcomes are physical domains of frailty (GarciaGarcia et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Atkinson et al [21] reported that baseline global cognitive functioning and changes in global cognitive functioning were associated with changes in physical performance, but baseline physical performance was not associated with cognitive changes in their elderly sample. On the other hand, several previous studies have shown that cognitive functioning greatly influence physical functioning [8,22,23]. Furthermore, the nutritional status correlated with cognitive function [24].…”
Section: Discussionmentioning
confidence: 99%
“…Even though geriatric frailty is described as global impairment of physiological reserves involving multiple organ systems, ADL decline in the elderly is due in large part to decrements in physical function [3,4]. Several studies have identified factors associated with physical function in elderly individuals [5][6][7][8]. In particular, nutritional state [7] and cognitive functioning [8] greatly influence physical functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the impact of cognitive status on functional limitations will help us to better understand the role cognitive function may play in the early stages of the disabling process. This would give weight to the assessment of cognitive function as a vital part of geriatric preventive measures to delay the onset of disability [8,9].…”
Section: Introductionmentioning
confidence: 99%